The lubrication effect of different vegetable oil-based greases on steel-steel tribo-pair - Rawat S.S.; Harsha A.P. (My University, 2025)
The rising environmental concerns and the challenges to enhance the tribo-performance of conventional lubricants have gained considerable attention these days. In this context, castor oil and coconut oil thickened with lithium soap were prepared for a stable and consistent grease. The physicochemical and tribological performances of castor and coconut greases were assessed as per the ASTM standards. The formulated lithium-based paraffin grease was used as reference grease to compare various physicochemical and lubrication behavior of castor and coconut greases. Castor grease demonstrated superior tribological performance than paraffin grease. The formation of a fatty acids–derived protective thin film of high shear strength enhanced the lubrication properties. It will be a new lubricant formulation, where energy conservation and environmental sustainability are the prime consideration. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.